2015
DOI: 10.1016/j.juro.2015.05.083
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain Management after Radical Cystectomy: Comparing Traditional versus Enhanced Recovery Protocol Pathway

Abstract: Patients on the protocol of enhanced recovery after surgery used significantly less opioid analgesics, possibly contributing to decreased postoperative ileus and shorter length of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 22 publications
1
57
0
1
Order By: Relevance
“…Overall, utilization of clinical pathways is associated with decreased narcotic usage, lower incidence of postoperative ileus, and shorter hospital length of stay. 22 …”
Section: Treatmentmentioning
confidence: 99%
“…Overall, utilization of clinical pathways is associated with decreased narcotic usage, lower incidence of postoperative ileus, and shorter hospital length of stay. 22 …”
Section: Treatmentmentioning
confidence: 99%
“…Multimodal opioid-sparing analgesia, combined with regional or local anesthesia, is recommended [1] and aims to provide effective pain management while minimizing the side effects of opioids. Xu et al [44] observed that patients on an ERAS protocol (opioid-sparing analgesics) used significantly less opioid analgesics after RC.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Although several studies have been published, striking variation exists in the effect of ERAS protocols on perioperative outcomes [415]. For example, some studies show that ERAS pathways can reduce the length of stay [4,6,10,11,14,16], whereas others do not [7,9,12,16]; some studies show that ERAS pathways can shorten the time to recovery of bowel activity [7,9,12], yet others do not [6,11]; some studies show that ERAS pathways can lower the rates of readmission [6,12,13]; but yet again, others do not [9,11,14].…”
Section: Introductionmentioning
confidence: 99%